Diversity, Biocontrol, and Plant Growth Promoting Abilities of Xylem Residing Bacteria from Solanaceous Crops - Gauri A. Achari; Raman Ramesh (International Journal of Microbiology)
Eggplant (Solanum melongena L.) is one of the solanaceous crops of economic and cultural importance and is widely cultivated in the state of Goa, India. Eggplant cultivation is severely affected by bacterial wilt caused by Ralstonia solanacearum that colonizes the xylem tissue. In this study, 167 bacteria were isolated from the xylem of healthy eggplant, chilli, and Solanum torvum Sw. by vacuum infiltration and maceration. Amplified rDNA restriction analysis (ARDRA) grouped these xylem residing bacteria (XRB) into 38 haplotypes. Twenty-eight strains inhibited growth of R. solanacearum and produced volatile and diffusible antagonistic compounds and plant growth promoting substances in vitro. Antagonistic strains XB86, XB169, XB177, and XB200 recorded a biocontrol efficacy greater than 85% against BW and exhibited 12%–22 % increase in shoot length in eggplant in the greenhouse screening. 16S rRNA based identification revealed the presence of 23 different bacterial genera. XRB with high biocontrol and plant growth promoting activities were identified as strains of Staphylococcus sp., Bacillus sp., Streptomyces sp., Enterobacter sp., and Agrobacterium sp. This study is the first report on identity of bacteria from the xylem of solanaceous crops having traits useful in cultivation of eggplant.